A questionnaire on mathematics learning strategies (CEAMA): measurement and properties of an adaptation into Spanish / Cuestionario de Estrategias de Aprendizaje para las Matemáticas (CEAMA): medida y propiedades de una adaptación en lengua castellana. Issue 1 (2nd January 2017) - Gasco-Txabarri, Javier; Ros, Iker; Goñi, Alfredo
Abstract: Learning strategies are an essential tool to enable the autonomous and active learning of mathematics and it is therefore necessary to identify these strategies correctly. The objective of this research is to analyse the factorial structure of the Spanish version of a questionnaire that measures the use of these strategies in the subject of mathematics (Cuestionario de Estrategias de Aprendizaje para las Matemáticas [CEAMA]). We adapt a questionnaire based on the MSLQ (Motivated Strategy for Learning Questionnaire), since it is focused on the context of mathematics learning. The study has been conducted in different schools located in the Basque Country and collects data from 631 students of the second, third and fourth years of compulsory secondary education (ESO). The results show a hepta-scale structure compared to the six-scale structure proposed by the original English version. The difference is detected in the division of metacognitive strategies into two factors: planning and monitoring/regulation. This finding improves data on metacognition in mathematics teaching and learning, making it richer and more exhaustive. The suitability of certain items is discussed.